2007
DOI: 10.3923/pjbs.2007.235.239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Application on Rice Yield under Wheat Rice System

Abstract: A field experiment was conducted during 2004-05 on wheat and rice to study the response of Zinc application in wheat-rice system. Two levels of zinc 5 and 10 kg ha(-1) with control were studied with the basal dose of N, P2O5, K2O as 120-90-60 kg ha(-1) in the form of urea, TSP, SOP and zinc sulphate during both the crops. Wheat variety Naseer 2000 and rice variety IRRI 6, both were planted in R.C.B design with three replications. Zn application, significantly affected wheat grain yield, ranged from 2.7 to 3.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 4 publications
16
53
0
Order By: Relevance
“…Yilmaz et al (1997) [22] reported that due to foliar spray of Zn fertilizer, wheat grain yield increase 100%. Our results were similar with Khan et al (2007) [23] who reported that wheat grain yield increases up to 31.6% by addition of 5 kg Zn per hectare over control.…”
Section: Grain Yield (Kg/ha)supporting
confidence: 82%
“…Yilmaz et al (1997) [22] reported that due to foliar spray of Zn fertilizer, wheat grain yield increase 100%. Our results were similar with Khan et al (2007) [23] who reported that wheat grain yield increases up to 31.6% by addition of 5 kg Zn per hectare over control.…”
Section: Grain Yield (Kg/ha)supporting
confidence: 82%
“…However, as only small amounts of B are required to regulate the meristematic growth (Khan et al, 2006) and any excessive amount becomes toxic impeding normal growth (Bonilla et al, 2004;Uraguchi et al, 2009). Shelp (1993 also opined that B is necessary for cell elongation and cell division, the events of growth.…”
Section: Discussionmentioning
confidence: 97%
“…Significant effects on achene yield were existed in our study when sunflower crop treated with nitrogen and boron nutrition. Improved achene yield with nitrogen and boron nutrition was due to its imperative role in pollen germination, flowering, proper seed setting, fruiting processes, sugar metabolism and balance between net photosynthetic rate and respiration (Khan et al, 2006). Its removal alters the cell wall structure integrity, caused hardening of plasma membrane led to reduce its activity for better transportation of photosynthates, eventually reduced seed yield.…”
Section: Discussionmentioning
confidence: 99%